2019
DOI: 10.1016/j.compstruct.2019.111247
|View full text |Cite
|
Sign up to set email alerts
|

Capacitance-based sensor with layered carbon-fiber reinforced polymer and titania-filled epoxy

Abstract: Advances in intelligent infrastructure can be achieved through the use of novel materials for increased systemlevel efficiency and multifunctionality. Carbon Fiber-Reinforced Polymer (CFRP) has been widely used in strengthening, rehabilitating, and retrofitting of existing structures because of its speed of deployment, low maintenance requirement, and high strength-to-weight ratio. In this work, the authors propose a novel method to augment CFRP with self-sensing capabilities. The sensor consists of two CFRP l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…It was found that there was not a big difference between the estimated gauge factor for type-A and -B, which was around 1.3. This gauge factor is relatively high compared with other structural health monitoring systems based on linear capacitive sensors such as 0.92 [31]. A slight difference was observed between the results obtained from samples A-1 and A-2 such as the difference in elastic modulus, which was around 7.4%.…”
Section: Performance Evaluation 41 Performance In the Longitudinal Di...mentioning
confidence: 77%
“…It was found that there was not a big difference between the estimated gauge factor for type-A and -B, which was around 1.3. This gauge factor is relatively high compared with other structural health monitoring systems based on linear capacitive sensors such as 0.92 [31]. A slight difference was observed between the results obtained from samples A-1 and A-2 such as the difference in elastic modulus, which was around 7.4%.…”
Section: Performance Evaluation 41 Performance In the Longitudinal Di...mentioning
confidence: 77%
“…Capacitance-based sensors have been proposed from bio-compatible polymers Burton et al (2019) and nanocomposite thin films Lee et al (2016). Research examples targeting biological skin mimicry for SHM applications include strain sensing sheets based on large area electronics and integrated circuits Tung et al (2014); Zhang et al (2014); Zhou et al (2010), electrical impedance tomography Hallaji et al (2014); Gupta et al (2016), and multifunctional materials Downey et al (2018); Yan et al (2019).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, strain sensors are intensively investigated for their skin-like features in robotic and prosthetic systems [4], or to detect human motions [5], but are also exploited for structural health monitoring [6]. pH sensors, on the other hand, giving information about the thermodynamics and kinetics of a variety of processes, are fundamental in fields from metabolism and nutrition [7], to catalysis and pharmaceutical chemistry [8], from food manufacturing and processing [9] to environmental science [10].…”
Section: Introductionmentioning
confidence: 99%